THE ROLE OF SOCIAL SUPPORT AND ORGANIZATIONAL CULTURE ON JOB BURNOUT ACCOUNT OFFICERS DURING PANDEMICS - I Gde Agung Wira Pertama; Ni Nyoman Sri Rahayu Damayanti; Ade Ruly Sumartini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
In pandemic conditions, the debtors showed their inability to pay the debt according to the agreed time period. Based on the problem, the government makes a debt restructuring policy for debtors who have difficulty in making payments and also distributes working capital debt to small businesses. In these conditions, an account officer is required to do an analysis of debt restructuring for debtors affected by the Covid 19 pandemic. The higher the number of debtors that affected by the pandemic, the higher the possibility of an account officer having an excess workload. High workload and job pressure can cause job burnout on the account officer. This research sample is an account officer who works at Bank Rakyat Indonesia Denpasar Renon Branch as well as all Auxiliary Branch Offices located under Denpasar Renon Branch Office. The data collection method used questionnaire techniques. The data analysis techniques used is multiple linear regression analysis. The results showed that social support variables had a negative and insignificant effect on job burnout. Subsequent results showed that organizational culture had a negative and significant effect on job burnout account officers. Keywords: Social Support, Organizational Culture, and Job Burnout.